유양돌기 방사선검사 시 조사야 사용법에 따른 영상의 유용성 평가 - 정홍량(Hong-Ryang Jung) (방사선기술과학, 2021)
The purpose of this study was to evaluate the quality of images and to quantitatively measure and analyze the dose of scattered ray to the organs, which were highly sensitive to radiation according to the use of cylinder cone in mastoid process radiography. When the cylinder cone was not used, the SID was 100cm and the field size was 24 × 36 cm(864 cm2). When using the cylinder cone which was a circle, the SID was 70 cm, the radius was 10.5 cm and field size was 86.59 cm2. As a result of the study, SNR of the image quality evaluation was measured to be 2.58 for Law method and 3.90 for Stenver's method when not using cylinder cone, and 2.87 for Law method and 14.67 for Stenver's method when using cylinder cone. CNR was measured to be 0.03 for Law method and 0.04 for Stenver's method when cylinder cone was not used, and 0.04 for Law method and 0.05 for Stenver's method when using cylinder cone. When the cylinder cone was not used, the scattered ray dose was measured to be 0.10 mGy in the right eyeball, 0.30 mGy in the left eyeball, 2.02 mGy in the parotid gland, and 0.29 mGy in the thyroid gland for Law method and to be 0.03 mGy in the right eyeball, 0.12 mGy in the left eyeball, 1.43 mGy in the parotid gland, and 0.09 mGy in the thyroid gland for Stenver's method. When the cylinder cone was used, the scattered ray dose was measured to be 0.05 mGy in the right eyeball, 0.03 mGy in the left eyeball and the parotid and thyroid gland were below the measurable values for Law method and all areas were below the measurable values for Stenver's method. This was found to be statistically significant(p<0.000).